Funções discursivas dos processos intertextuais por copresença em gênero resenha acadêmico-crítica - Chaves Júnior, José Araújo (2020)
After an initial characterization of the notion of intertextuality, as proposed by Kristeva in the 1970s, in the field of theoretical and literary criticism, as well as a characterization of the categorizations and systematizations developed by Genette (1982) and, later, by Piégay-Gros (1996), studies related to this thematic have advanced a great deal in the context of Textual Linguistics, in the last few years, starting mainly from the works of Koch (2004, 2009). Our interest in the theme is associated to the stricter categories, as expanded by Piégay-Gros (1996), mainly for intertextual relations by co-presence (citation, reference, and allusion) and for the contributions of Koch, Bentes and Cavalcante (2007), in the search for a refinement of those categories. We also work with paraphrases, as in Sant'Anna (1988) and Fuchs (1983), as an alternative for typological approximation. In this sense, our main objective is to analyze the discursive functions in these intertextual relations in the academic-critical review genre, analyzing the interrelations that are operated in the formal/functional structure of the genre in question. Therefore, we directed this research towards intertextuality, to verify the more recurring discursive functions, such as: exemplification, illustration, argumentative reinforcement, and argument of authority (PERELMAN; TYTECA, 2005); resumption of information, topic (PINHEIRO, 2005; JUBRAN, 2006); and ornamentation (PIÉGAY-GROS, 1996). Although this research is within the background of Textual Linguistics, we dialogue with other studies, such as the works of Silva (2009), Forte (2013) and Nobre (2014). Regarding the methodological aspect, so that our objectives can be achieved, we use the descriptiveinterpretative method (MOITA-LOPES, 1995), given the linguistic-discursive influence which holds this research, within the scope of a social science. Therefore, we analyzed a corpus composed of 20 (twenty) academic-critical reviews, which were previously theoretically and methodologically delimited, mainly based on the rhetorical analysis models of the review by Motta-Roth (1995) and Bezerra (2001). Regarding the results, we found that the intertextual types by co-presence - citation, reference, and allusion - already bring in their definition various discursive functions, in addition to being associated with the socio-rhetorical constitution of the genre and can thus promote other functions. Among the results, we highlight the identification of discursive functions associated only with the textual genre, without the need of an interconnection with intertextual types. Thus, while working with intertextual types and discursive functions in conjunction with aspects of the genre, we consider the alignment between the categories of intertextuality, the categories of the field of speech and the study of genres as an effective theoretical-methodological approach for the treatment of the academicalcritical review.